Atypical Presentation of an Ovarian Yolk Sac Tumor in an 80-Year-Old Woman: A Case Report and Review of the Literature - Vanessa Maldonado; María Masvidal; Vanessa Morente Laguna; Jacqueline Cimerman; Salvador Martinez Soriano (Case Reports in Oncology)
Introduction: Ovarian yolk sac tumors after the menopause are very rare. Case Presentation: We report an atypical case of yolk sac tumor in an octogenarian woman, who presented to the hospital with anasarca, ascites, toxic syndrome, and an abdominal mass. Serum alpha-fetoprotein (AFP) levels were highly increased (246,720 ng/mL), and malignant cells with positive AFP immunohistochemical expression were detected in a diagnostic paracentesis. The definitive diagnosis was established by histopathological examination of the surgical specimen and immunohistochemical detection of positivity for AFP, glypican 3, cytokeratin AE1/AE3, and focal positivity for SALL4 and CK7. Adjuvant chemotherapy was refused by the patient. Postoperative AFP values decreased to normal limits. One year after surgery, she remains in good clinical condition without evidence of tumor recurrence. In a review of the literature, 11 cases of yolk sac tumors in postmenopausal women were collected. The mean age of the patients was 63.4 years (range 58–82 years). Frequent findings were FIGO stage II, cytoreductive surgery, immunohistochemical analyses of a large panel of markers, postoperative chemotherapy, and no tumor recurrence (except in 1 patient who died), although the length of follow-up was relatively short or unclearly stated. Conclusion: The present case report illustrates that yolk sac tumors in very old women may have a favorable clinical course without signs of recurrence even in the absence of radical surgical resection with curative intent and associated adjuvant chemotherapy.